2018
DOI: 10.1021/jacs.8b00900
|View full text |Cite
|
Sign up to set email alerts
|

Nanocage-Confined Synthesis of Fluorescent Polycyclic Aromatic Hydrocarbons in Zeolite

Abstract: Polycyclic aromatic hydrocarbons (PAHs) attract much attention for applications to organic light-emitting diodes, field-effect transistors, and photovoltaic cells. The current synthetic approaches to PAHs involve high-temperature flash pyrolysis or complicated step-by-step organic reactions, which lead to low yields of PAHs. Herein, we report a facile and scalable synthesis of PAHs, which is carried out simply by flowing acetylene gas into zeolite under mild heating, typically at 400 °C and generates the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Over the past few years, the polycyclic aromatic hydrocarbons (PAHs) , have been considered to be a hot spot, because of their inexpensive production, structural tailorability, and excellent optoelectronic properties. These inherent superiorities drew tremendous interest for the potential applications of PAHs in diverse research fields such as advanced organic devices, biosensors, materials science, and asymmetric catalysis. Among them, the electrochemiluminescence (ECL) properties of PAHs (such as 9,10-diphenylanthracene (DPA), perylene, rubrene (Rub), phenanthrene derivatives) were particularly eye-catching, since the systemic study of ECL was reported in 1964 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, the polycyclic aromatic hydrocarbons (PAHs) , have been considered to be a hot spot, because of their inexpensive production, structural tailorability, and excellent optoelectronic properties. These inherent superiorities drew tremendous interest for the potential applications of PAHs in diverse research fields such as advanced organic devices, biosensors, materials science, and asymmetric catalysis. Among them, the electrochemiluminescence (ECL) properties of PAHs (such as 9,10-diphenylanthracene (DPA), perylene, rubrene (Rub), phenanthrene derivatives) were particularly eye-catching, since the systemic study of ECL was reported in 1964 .…”
mentioning
confidence: 99%
“…O ver the past few years, the polycyclic aromatic hydrocarbons (PAHs) 1,2 have been considered to be a hot spot, because of their inexpensive production, structural tailorability, and excellent optoelectronic properties. These inherent superiorities drew tremendous interest for the potential applications of PAHs in diverse research fields such as advanced organic devices, biosensors, materials science, and asymmetric catalysis.…”
mentioning
confidence: 99%
“…When referring to zeolite-templated 3D porous carbons, the investigations from Ryoo et al cannot be ignored. [20,21,81,92,99,[230][231][232] Since 1990s, Ryoo et al synthesized and prepared a series of nanocarbon materials templated by zeolites. Massive efforts from Ryoo et al were invested to elucidate the effect of cations of zeolites in synthesis and preparation of nanocarbon materials, as shown in Figure 12.…”
Section: D Porous Carbonsmentioning
confidence: 99%
“…cannot be ignored. [ 20,21,81,92,99,230–232 ] Since 1990s, Ryoo et al. synthesized and prepared a series of nanocarbon materials templated by zeolites.…”
Section: Structure and Morphology Of Zeolite‐templated Nanocarbons Inmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) has aroused great interest by virtue of its high sensitivity, wide range, and low background signals. Compared with traditional ECL emitters, such as luminol and Ru­(bpy) 3 2+ , polycyclic aromatic hydrocarbons (PAHs) and derivatives as ECL luminophores have received great attention for ECL bioanalysis and imaging over the past few decades due to their high fluorescence (FL) quantum efficiency, relatively low cost, and structural tailorability. Perylene (Pe) is a PAH molecule with a large π-conjugated structure, which has been extensively explored owing to its excellent photochemical properties. However, the unexpected aggregation-caused quenching (ACQ) effect was unavoidable when it was in solid or aggregated states, because Pe as a typical plane molecule was prone to form aggregates via intermolecular π–π stacking, which will decrease their emission efficiency.…”
Section: Introductionmentioning
confidence: 99%